Carbon dots as a trackable drug delivery carrier for localized cancer therapy in vivo. Issue 30 (8th July 2016) - Zeng, Qinghui; Shao, Dan; He, Xu; Ren, Zhongyuan; Ji, Wenyu; Shan, Chongxin; Qu, Songnan; Li, Jing; Chen, Li; Li, Qin
Abstract : Green carbon dots with a carboxyl-rich surface were employed as a selective nanocarrier for fluorescent traceable and pH-sensitive Doxorubicin delivery in localized cancer treatment. Abstract : Fluorescent carbon dots (CDs) with a size smaller than 10 nm, excellent biocompatibility, and low to no cytotoxicity are considered as a rising star in nanomedicine. In this report, for the first time we demonstrate that green-emitting CDs with a carboxyl-rich surface can be employed as a trackable drug delivery agent for localized cancer treatment in a mouse model. The CDs are conjugated with the cancer drug, Doxorubicin (DOX), via non-covalent bonding, utilizing the native carboxyl groups on CDs and the amine moiety on DOX molecules. The pH difference between cancer and normal cells was successfully exploited as the triggering mechanism for DOX release. Our in vivo study demonstrated that the fluorescent CDs can serve as a targeted drug delivery system for localized therapy, and the stimuli-responsive non-covalent bonding between the nanodot carrier and the drug molecule is sufficiently stable in complex biological systems. Taken together, our work provides a strategy to promote the potential clinical application of CDs in cancer theranostics.